The Simulated Virology Clinic: A Standardized Patient Exercise for Preclinical Medical Students Supporting Basic and Clinical Science Integration - Jennifer M. Jackson (Association of American Medical Colleges, 2020)
Introduction Virology is inherently challenging due to the sheer volume of information medical students are responsible for learning. Cognitive integration of this content is critical for early medical students to practice applying this knowledge to diagnostic problem-solving. Simulation offers learners engaging opportunities to practice cognitive integration. We developed a simulated clinic activity for first-year medical students consisting of standardized patient (SP) encounters representing viral infections. Methods Student small groups rotated through eight SP encounters during which they collected patient histories, reviewed physical exam findings, and developed a differential diagnosis and diagnostic plan for each case. The instructor debriefed students on the cases afterward. We assessed students' evaluation of the activity through online surveys. Results Two hundred seventy-eight students participated in the simulated clinic in 2018 and 2019. Students rated the activity as very effective for learning about the infections represented and for providing opportunities to integrate clinical skills. Students agreed that the event's instructional design was appropriate for its objectives and that the problem-solving aspect was intellectually stimulating. They indicated that the most effective aspects were solidifying illness scripts for the infections represented, integrating knowledge and skills to diagnose patients in a realistic clinical context, and working collaboratively to problem-solve. Discussion The simulated virology clinic is an effective method for providing students opportunities to integrate microbiology and clinical skills and has been positively received by students. This instructional method offers learners an opportunity to solidify illness scripts for viral infections using an interactive, collaborative approach.